Ahlul Bait Nabi Noble's Characters as Inspiration in Educational Management - Badaruddin, Kemas; Zailia, Siti; Ramadhan, Syahrul; Arafah Pramasto (Yayasan Sinergi Kawula Muda, 2025)
The descendants of the Prophet Muhammad or commonly called the